Analysis of Differences in the Use of Kahoot and Quizizz Applications in Improving Analytical Thinking of Physics Education Students, Universitas Negeri Yogyakarta - Amalia, Ayu; Daynuari, Mellina Ayu; Setiaji, Bayu (Impulse: Journal of Research and Innovation in Physics Education, 2023)
Learning media is one of the important things in determining the results of the learning process. Interesting learning activities by focusing the interaction between lecturers and students will increase motivation in learning. Therefore, it needs to be packaged well, one of which is an interactive quiz after learning. There are several online quizzes that are often used, namely Kahoot and Quiziz, these quizzes provide services for users to create their own quizzes and can share them with others to take quizzes. The purpose of this study was to determine whether there was a difference in the use of the Kahoot and Quizizz quizzes in improving the analytical thinking of students of Physics Education C UNY 2020 on light interference material. The research method used is an experimental research method in quasi experiment with posttest only design where the research subject will do an analytical ability test given in the form of multiple choice questions given through Kahoot and Quizizz. After that, data analysis will be carried out using a t-test, the results of the analysis show that there are differences in the use of the two quizzes, namely Kahoot and Quizizz with a significance value of 0.642.